Antidiabetic and Antioxidant Properties of Alkaloids from Catharanthus roseus (L.) G. Don - Tiong, Soon Huat; Looi, Chung Yeng; Hazni, Hazrina; Arya, Aditya; Paydar, Mohammadjavad; Wong, Won Fen; Cheah, Shiau Chuen; Mustafa, Mohd Rais; Awang, Khalijah (MDPI, 2013)
Abstract: Catharanthus roseus (L.) G. Don is a herbal plant traditionally used by local populations in India, South Africa, China and Malaysia to treat diabetes. The present study reports the in vitro antioxidant and antidiabetic activities of the major alkaloids isolated from Catharanthus roseus (L.) G. Don leaves extract. Four alkaloids—vindoline I, vindolidine II, vindolicine III and vindolinine IV—were isolated and identified from the dichloromethane extract (DE) of this plant’s leaves. DE and compounds I–III were not cytotoxic towards pancreatic β-TC6 cells at the highest dosage tested (25.0 μg/mL). All four alkaloids induced relatively high glucose uptake in pancreatic β-TC6 or myoblast C2C12 cells, with III showing the highest activity. In addition, compounds II–IV demonstrated good protein tyrosine phosphatase-1B (PTP-1B) inhibition activity, implying their therapeutic potential against type 2 diabetes. III showed the highest antioxidant potential in ORAC and DPPH assays and it also alleviated H2O2-induced oxidative damage in β-TC6 cells at 12.5 μg/mL and 25.0 μg/mL.